Perception of Generation Z on Stock Market Investment in Rajkot City - Pravin, Pratik; Parmar, Shailesh J. (Journal of Social Commerce, 2024)
This study examines the knowledge, investment activity and perception of Generation Z towards the stock market. Researcher has collected data from 221 participants through structured questionnaire from Gen-Z of Rajkot City, Gujarat (India). The main objectives of the study are to analyse the perception of generation z towards the stock market and to check the difference in the perception related to different factors like gender, stream of education investment attitude etc. In this research researcher has used chi-square and T test to test the hypotheses.  The results showed that males were more likely to invest in stock market than females and that social media and school/college were the most popular influencing sources of information to invest in the stock market. During analysis, it was found that education was a key factor in the investment decisions of Generation Z. To improve the investment potential of Generation Z, targeted efforts should be taken to encourage female participation in the stock market and to provide more resources for women to gain the knowledge and confidence to invest in the stock market. This research also affects three of the Sustainable Development Goals (SDGs): Goal 8, 10 and, 17.